Belief and Disbelief in the Space Between, 1914-1945 - Jean-Christophe MURAT (E-REA)
This article explores the political and spiritual journey of Douglas Hyde (1911-1996), from Methodism through communism to Roman Catholicism, as described in I Believed, his autobiography published in 1950. Hyde, a prominent member of the British Communist Party (CPGB) from 1928 to 1948, occupies a position in the history of twentieth-century communism that is at once typical and unusual. His becoming a member of the Communist Party in 1928 represented a form of “going-over” shared by many young men and women of his generation. In his particular case, this meant turning his back on the middle-class nonconformist milieu he had been born into, and which had shaped his initial project to become a Methodist preacher, and deciding instead to help forward the civil war that should lead to a Soviet-inspired revolution in Britain. Hyde’s communism, however, never sat comfortably with the official line, despite the fact that he spent almost two decades tirelessly organising all sorts of Party-led campaigns, and about ten years working as news editor for the Daily Worker. If Hyde’s resignation from the British Communist Party in 1948 was highly publicised by the media, it was mostly the official announcement of his conversion to Roman Catholicism, which he had fought savagely before and during World War Two, that met with the disbelief, and soon earned him the hatred of his former Party comrades. The rather irksome note of complacency that rings through the last chapters of I Believed may be read like the enthusiasm of the new convert who has had his Truth revealed at last; it may also disclose the fact that Hyde’s autobiographical enterprise had been nothing but a wholesale indictment of communism all along.